'Panman' Movie Stars in NY Movie Festival - Unknown (Trinidad Guardian)
‘The Panman’, a movie filmed in Trinidad and released in 1997, has been selected as one of the features of the International Independent Film and Video Festival in New York in September 2001 and Los Angeles in November.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Film festivals -- United States; Video recordings -- Production and direction -- Trinidad and Tobago; Steel band music